2016
DOI: 10.1111/psyg.12181
|View full text |Cite
|
Sign up to set email alerts
|

Rapid eye movement sleep without atonia may help diagnose Lewy body disease in middle‐aged and older patients with somatic symptom disorder

Abstract: REM sleep without atonia may provide an opportunity to identify LBD in patients with somatic symptom disorder, even before they fulfil the clinical criteria for PD or DLB. Continued follow-up will be needed to determine whether these psychiatric patients are in the prodromal stage of PD or DLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In previous studies on patients with PD, constipation was already associated with the presence of RBD and depression . These non‐motor symptoms have been demonstrated to occur many years before the onset of motor symptoms of PD, and are referred to as a condition called ‘pre‐motor PD’ .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on patients with PD, constipation was already associated with the presence of RBD and depression . These non‐motor symptoms have been demonstrated to occur many years before the onset of motor symptoms of PD, and are referred to as a condition called ‘pre‐motor PD’ .…”
Section: Discussionmentioning
confidence: 99%
“…In DLB patients, the incidence of RBD was up to 76%, anticipating the emergence of DLB by several years ( 30 ). Takayuki et al showed a correlation between RBD and DLB ( 31 ). In early-onset DLB patients with RBD, Kasanuki K et al found a significant deterioration of the dopaminergic pathways ( 32 ).…”
Section: Discussionmentioning
confidence: 99%